RESOLVING CRIMINAL ACTS OF NARCOTICS THROUGH A RESTORATIVE JUSTICE APPROACH IN EAST JAVA - Syarib Rama Indradi Mukti; Bambang Sugiri; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
This study discussed the handling of narcotics abuse crimes through a restorative justice approach based on the Indonesian National Police Regulation Number 8 of 2021 regarding the Handling of Criminal Acts Based on Restorative Justice. According to this regulation, individuals involved in narcotics abuse could undergo a restorative justice approach, giving them the opportunity to undergo medical or social rehabilitation without having wait for a court decision. The aim of this study was to analyze the basic principles considered and the strategies used by the Police in handling narcotics abuse cases through the restorative justice approach. In determining these consederations, it was important to ensure that the steps taken were in accordance with applicable legal provisions, as well as addressing the challenges in implementing restorative justice, which required effective strategies, so that these considerations and strategies could result in legal benefit and justice. This study was an empirical research using a socio-legal or juridical-empirical method with a legal sociology approach. The study used primary data obtained through interviews with informants, and the secondary data in the form of bibliographical sources. The research data were analyzed using a qualitative descriptive method. The results of this study has ben showed that the investigators considerations in handling narcotics crimes through the restorative justice approach were based on the requirements and mechanisms for handling them in accordance with the Police Regulation. The investigators strategy was to enhance understanding of the concept of restorative justice in order to overcome the challenges such as the low submission of Integrated Assesments and the lack of understanding among offenders about the concepts of restorative justice.